O “Inolvidável Polígrafo” : regionalismo literário gaúcho e nacionalismo brasileiro em Apolinário Porto Alegre (1869-1879) - Menez, Alexsandro da Rosa (2015)
The Regionalism from Rio Grande do Sul and the regionalist literature that set the tone for this movement were, from the early twentieth century, objects of several researches that generated a lot of interpretations. An ever-present discussion in those works concerns the relationship between the regional and national, in which the constitution of the regional's identity would have conducted through or not, differentiation toward the Brazilian identity. In other words, the contours between the regional affirmation and the inserting in the Brazilian nation were never very clear. As a result, this characteristic has always generated much controversy, from no academic studies to those developed in the university academic environment. In this context, the polygraph Apolinário Porto Alegre comes and, according to historiography from Rio Grande do Sul, he would have been the trigger, from the second half of the nineteenth, of the Gaúcho regionalism. On the other hand, the same historiography, especially after the academic specialization, began pointing that he had concerns about the Brazilian nationality in his horizon. Therefore, this work is inserted in the middle of these hazy historiographical discourses, seeking to ascertain the relationship between the Gaúcho regionalism and Brazilian nationalism in Apolinario Porto Alegre.